Design, Fabrication, and Integration of an Electrostatic Analyzer for a Satellite Payload. - Morel,Paul R.; Hanser,Rederick A.; Sellers,Bach (1974)
A satellite-borne electron spectrum analyzer has been developed. This instrument performs a 32 channel differential analysis of 0.08 to 17 keV electrons, via electrostatic deflection. The described instrument is a modified version of units successfully launched into auroral breakups at Ft. Churchill, Manitoba, Canada. The modified design minimizes weight and power requirements, and provides an interface compatible with the S3 satellites. Two instruments have been fabricated, tested and calibrated. One has been integrated into the S3-2 satellite, scheduled for launch in 1975. The second instrument (a backup to the flight unit) is scheduled to be subjected to a long term vacuum test (3-6 months duration) at AFCRL.